DNA Hydroxymethylation in High-Grade Gliomas - Stapińska-Syniec, Angelika; Grabiec, Marta; Rylski, Marcin; Acewicz, Albert; Sobstyl, Michał (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2022)
Background Since the new World Health Organization (WHO) classification of nervous system tumors (2016, revised, 4th edition) has been released, gliomas are classified depending on molecular and genetic markers in connection with histopathology, instead of histopathology itself as it was in the previous classification. Over the last years, epigenetic analysis has taken on increased importance in the diagnosis and treatment of different cancers. Multiple studies confirmed that deoxyribonucleic acid (DNA) methylation and hydroxymethylation play an important role in the regulation of gene expression during carcinogenesis.Methods In this review, we aim to present the current state of knowledge on DNA hydroxymethylation in human high-grade gliomas (WHO grades III and IV).Results The correlation between DNA hydroxymethylation and survival in glioblastoma multiforme (GBM) patients was evaluated by different studies. The majority of them showed that the expression of 5-hydroxymethylcytosine (5-hmC) and ten-eleven translocation (TET) enzymes were significantly reduced, sometimes almost undetectable in high-grade gliomas in comparison with the normal brain. A decreased level of 5-hmC was associated with poor survival in patients, but high expression of the TET3 enzyme was related to a better prognosis for GBM patients. This points to the relevance of DNA hydroxymethylation in molecular diagnostics of human gliomas, including survival estimation or differentiating patients in terms of response to the treatment.Conclusion Future studies may shed some more light on this epigenetic mechanism involved in the pathogenesis of human high-grade gliomas and help develop new targeted therapies.
Keywords: DNA hydroxymethylation; 5-hydroxymethylcytosine; glioma; glioblastoma multiforme; survival